Genetics impact risk of Alzheimer’s disease through mechanisms modulating structural brain morphology in late life: neurodegeneration - Korologou-Linden, Roxanna; Xu, Bing; Coulthard, Elizabeth; Walton, Esther; Wearn, Alfie; Hemani, Gibran; White, Tonya; Cecil, Charlotte; Sharp, Tamsin; Tiemeier, Henning; Banaschewski, Tobias; Bokde, Arun; et al. (Journal of neurology, neurosurgery, and psychiatry, 2024)
Background Alzheimer’s disease (AD)-related neuropathological changes can occur decades before clinical symptoms. We aimed to investigate whether neurodevelopment and/or neurodegeneration affects the risk of AD, through reducing structural brain reserve and/or increasing brain atrophy, respectively. - Methods We used bidirectional two-sample Mendelian randomisation to estimate the effects between genetic liability to AD and global and regional cortical thickness, estimated total intracranial volume, volume of subcortical structures and total white matter in 37 680 participants aged 8-81 years across 5 independent cohorts (Adolescent Brain Cognitive Development, Generation R, IMAGEN, Avon Longitudinal Study of Parents and Children and UK Biobank). We also examined the effects of global and regional cortical thickness and subcortical volumes from the Enhancing NeuroImaging Genetics through Meta‐Analysis (ENIGMA) Consortium on AD risk in up to 37 741 participants. - Results Our findings show that AD risk alleles have an age-dependent effect on a range of cortical and subcortical brain measures that starts in mid-life, in non-clinical populations. Evidence for such effects across childhood and young adulthood is weak. Some of the identified structures are not typically implicated in AD, such as those in the striatum (eg, thalamus), with consistent effects from childhood to late adulthood. There was little evidence to suggest brain morphology alters AD risk. - Conclusions Genetic liability to AD is likely to affect risk of AD primarily through mechanisms affecting indicators of brain morphology in later life, rather than structural brain reserve. Future studies with repeated measures are required for a better understanding and certainty of the mechanisms at play.